Linking Early Life Hypothalamic–Pituitary–Adrenal Axis Functioning, Brain Asymmetries, and Personality Traits in Dyslexia: An Informative Case Study - Zakopoulou, Victoria; Vlaikou, Angeliki-Maria; Darsinou, Marousa; Papadopoulou, Zoe; Theodoridou, Daniela; Papageorgiou, Kyriaki; Alexiou, George A.; Bougias, Haralambos; Siafaka, Vassiliki; Zoccolotti, Pierluigi; Chroussos, George P.; Syrrou, Maria; et al. (Frontiers in Human Neuroscience, 2019)
Developmental Dyslexia (DD) is a multi-system disorder, combining influences of susceptibility genes and environmental factors. The causative interaction between specific genetic factors, brain regions and personality/mental disorders, as well as specific learning disabilities, has been thoroughly investigated with regards to the approach of developing a multifaceted diagnostic procedure with an intervention strategy potential. In an attempt to add new translational evidence to the interconnection of the above factors in the occurrence of DD, we performed a combinatorial analysis of brain asymmetries, personality traits, cognitive and learning skills, and expression profiles of selected genes in an adult, early diagnosed with DD, and in his son of typical development. We focused on the expression of genes, based on the assumption that the regulation of transcription may be affected by genetic and epigenetic factors. The results highlighted a potential chain-link between neuroplasticity-related as well as stress-related genes, such as BDNF, Sox4, MR and GILZ, leftward asymmetries in the amygdala and selective cerebellum lobules, and tendencies for personality disorders and dyslexia. This correlation may reflect the presence of a specific neuro-epigenetic component of developmental dyslexia, ensuing from the continuous, multifaceted difficulties in the acquisition of cognitive and learning skills, which in turn may act as a fostering mechanism for the onset of long-term disorders. This is in line with recent findings demonstrating a dysfunction in processes supported by rapid neural adaptation in children and adults with dyslexia. Accordingly, the co-evaluation of all the above parameters may indicate a stress-related dyslexia endophenotype which should be carefully considered for a more integrated diagnosis and effective intervention.